Kitabah Error Analysis Based on Theory of Rusydi Ahmad Thuaimah: Analisa Kesalahan Kitabah Berbasis Teori Rusydi Ahmad Thuaimah - Khizanatul Hikmah; Anis Farikha; Muhlasin Amrullah; Bachtiar Adi Saputra (Universitas Muhammadiyah Sidoarjo, 2020)
This research is about writing error analysis based on Rusydi Ahmad Thuaimah's the- ory which aims to analyze writing errors in students of Islamic Education in 3rd semester 2018-2019 UMSIDA. Respondents in this study were students of PAI 3rd semester 2018- 2019. Data collection in this study uses documentation methods, questionnaires, and literature studies. The results of this study are factors in writing (Imlak) of 3rd semester students of islamic studies in 2018-2019 UMSIDA, Factor internal language: Not yet know the writing of harakat hijaiyah properly and correctly, difficulty in distinguishing hijaiyah let- ters with almost the same pronunciation, difficulty in distinguishing letters that are spoken with written ones. The solution to the obstacles faced by students of islamic studies in 3rd semester 2018-2019 UMSIDA in Maharah Kitabah (Imlak) is by building a mindset and easy motivation and being able to write Arabic words or sentences in accordance with the correct rules, making students familiar with imlak by maximizing the lecture time, given concepts related to the absolute rules correctly.